Deteksi dan Kuantifikasi Hidrokuinon pada Sampel Night Cream di Kecamatan X Sukoharjo - Retno Kurnia Dewi; Danang Raharjo; Bagas Ardiyantoro (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Hydroquinone is a skin lightening agent that effectively inhibits melanogenesis, but its use in cosmetics is restricted due to the potential for serious side effects. Although banned in over-the-counter cosmetics, hydroquinone is still found in unregistered night cream products. This study aims to detect the presence, determine the levels of hydroquinone, and evaluate its safety risks in night cream products sold in District X, Sukoharjo Regency. The study was conducted experimentally in a laboratory using a purposive sampling technique on 15 night cream samples consisting of 8 BPOM-registered products and 7 non-BPOM products. Qualitative analysis was carried out using FeCl₃, Benedict's, and o-phenanthroline color reaction tests, while quantitative analysis used the HPLC method with a C18 column and a UV-Vis detector at a wavelength of 280 nm. The results showed that all BPOM-registered samples did not contain hydroquinone, while several non-BPOM samples were detected to contain hydroquinone at levels ranging from 0.0688%–0.2043%. These findings indicate a higher safety risk in non-BPOM products. The implications of this research emphasize the importance of strengthening regulatory oversight and increasing public literacy in choosing safe and legal cosmetic products.